(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
The current research investigates the linkage between Micro credit on SMEs business growth and poverty alliviation in rural Sindh. Data will be collected from 300 respondents who used Micro credit by using the simple random sampling technique and data were analysis by using SPSS-21 version. It was revealed that micro credit increases employment and productivity or not is an empirical question which we will explore in this section. Consequently, the best way to reduce poverty is to deal with both problems: increasing productivity by creating employment and developing human capital. One way to increase the productivity of the poor is through broad-based economic growth.